2020
DOI: 10.1056/nejmc2016359
|View full text |Cite
|
Sign up to set email alerts
|

Saliva or Nasopharyngeal Swab Specimens for Detection of SARS-CoV-2

Abstract: Rapid and accurate SARS-CoV-2 diagnostic testing is essential for controlling the ongoing COVID-19 pandemic. The current gold standard for COVID-19 diagnosis is real-time RT-PCR detection of SARS-CoV-2 from nasopharyngeal swabs. Low sensitivity, exposure risks to healthcare workers, and global shortages of swabs and personal protective equipment, however, necessitate the validation of new diagnostic approaches. Saliva is a promising candidate for SARS-CoV-2 diagnostics because (1) collection is minimally invas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
998
7
28

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 895 publications
(1,099 citation statements)
references
References 21 publications
48
998
7
28
Order By: Relevance
“…2). [7][8][9]. In the present study, unexpectedly, a high number of samples with Ct values on the border of Ct < 40 and low sensitivity of our results for patients (53.4%) were observed.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…2). [7][8][9]. In the present study, unexpectedly, a high number of samples with Ct values on the border of Ct < 40 and low sensitivity of our results for patients (53.4%) were observed.…”
Section: Resultscontrasting
confidence: 61%
“…An Italian study performed with 25 patients with COVID-19 concluded that saliva is a reliable medium for detecting SARS-CoV-2 [8]. A study performed with 70 inpatients with COVID-19 showed that saliva specimens and nasopharyngeal swabs have similar sensitivity during the course of hospitalization in the detection of SARS-CoV-2 using a primer set from the Centers for Disease Control and Prevention [9].…”
Section: Introductionmentioning
confidence: 99%
“…Viral RNA measurement SARS-CoV-2 RNA concentrations were measured from nasopharyngeal samples and saliva samples by RT-PCR as previously described 18,19 . In short, total nucleic acid was extracted from 300 μl of viral transport media from the nasopharyngeal swab or 300 μl of whole saliva using the MagMAX Viral/Pathogen Nucleic Acid Isolation kit (ThermoFisher Scientific) using a modified protocol and eluted into 75 μl of elution buffer 19 . For SARS-CoV-2 RNA detection, 5 μl of RNA template was tested as previously described 18 , using the US CDC real-time RT-PCR primer/ probe sets for 2019-nCoV_N1, 2019-nCoV_N2, and the human RNase P (RP) as an extraction control.…”
Section: Patients and Hcwsmentioning
confidence: 99%
“…Of the individuals included in the study, 27 of the 46 with active infections and 40 of the 68 overall were from staff and vendors. The median number of tests administered to each of the 68 individuals was 41 (IQR [14,51]; Range [5,70]). The median number of positive Ct values recorded for each person was 3 (IQR [2,4]; Range [1,9]).…”
Section: Main Textmentioning
confidence: 99%